Основные результаты работ Донузлавской экспедиции в Сакском и Черноморском районах Крыма в 2009 г. - Ланцов, С.Б. (Археологічні дослідження в Україні, 2010)
Presented are the excavations at Kulchuk hill-fort dated from the 4th c. BC to the edge of the millennia and from the 8th c. to the 9th c. situated on the coast of the Black Sea in the North-Western Crimea as a result of which a secret underground passage of the Hellenistic period was discovered. Archeological and geophysical prospecting at Ancient settlements of the southern shore of Tarkhankut Peninsula in Chornomorske Region was also conducted. In Saky the protective zone of «Saky peresyp» archaeological site (Ancient sanctuary and settlement of the 9th— 10th c.) was specified.